The balance of interleukin‐12 and interleukin‐23 determines the bias of MAIT1 versus MAIT17 responses during bacterial infection. Issue 7 (2nd June 2022) - Wang, Huimeng; Nelson, Adam G; Wang, Bingjie; Zhao, Zhe; Lim, Xin Yi; Shi, Mai; Meehan, Lucy J; Jia, Xiaoxiao; Kedzierska, Katherine; Meehan, Bronwyn S; Eckle, Sidonia BG; Souter, Michael NT; et al.
Abstract: Mucosal‐associated invariant T (MAIT) cells are a major subset of innate‐like T cells mediating protection against bacterial infection through recognition of microbial metabolites derived from riboflavin biosynthesis. Mouse MAIT cells egress from the thymus as two main subpopulations with distinct functions, namely, T‐bet‐expressing MAIT1 and RORγt‐expressing MAIT17 cells. Previously, we reported that inducible T‐cell costimulator and interleukin (IL)‐23 provide essential signals for optimal MHC‐related protein 1 (MR1)‐dependent activation and expansion of MAIT17 cells in vivo . Here, in a model of tularemia, in which MAIT1 responses predominate, we demonstrate that IL‐12 and IL‐23 promote MAIT1 cell expansion during acute infection and that IL‐12 is indispensable for MAIT1 phenotype and function. Furthermore, we showed that the bias toward MAIT1 or MAIT17 responses we observed during different bacterial infections was determined and modulated by the balance between IL‐12 and IL‐23 and that these responses could be recapitulated by cytokine coadministration with antigen. Our results indicate a potential for tailored immunotherapeutic interventions via MAIT cell manipulation. Abstract : Mucosal‐associated invariant T (MAIT) cells in mice exist as two subsets: T‐bet‐expressing MAIT1 and RORγt‐expressing MAIT17 cells. We show that interleukin (IL)‐12 and IL‐23 promote MAIT1 cell expansion during acute infection with Francisella tularensis, and that the bias toward MAIT1 or MAIT17 responses seen during different bacterial infections is determined by the balance between these cytokines. Excitingly, these responses can be recapitulated by varying the ratio of cytokines coadministered with antigen, indicating a potential for therapeutic manipulation of MAIT cells.